THE INVESTIGATION OF THE RELATIONSHIP BETWEEN EIGHTH GRADERS’ ACADEMIC ACHIEVEMENT AND THEIR ATTITUDES TOWARDS REPUBLIC OF TURKEY REVOLUTION HISTORY AND KEMALISM COURSE IN TERMS OF SOME VARIABLES - Ayşegül YILMAZER (Fırat University, 2019)
The aim of this study is to investigate the relationship between eighth graders’ academic achievement and their attitudes towards Republic of Turkey Revolution History and Kemalism (RTRHK) course in terms of some variables. The participants of this study were composed of 1000 eighth graders studying in Sivas province during 2014-2015 academic year. In this study focusing on the relationship between eighth graders’ academic achievement and their attitudes towards RTRHK course, the data were collected using RTRHK course Attitude Scale, which was developed as a 23-item scale by Yeşiltaş and Yılmazer (2015) and personal information form, which was composed of 19 items. The obtained data were entered into IBM SPSS Statistic 23 software, and made ready for the analysis. Within this context, frequency, percentages, mean scores, mean rank, standard deviation, independent samples t-test, one-way analysis of variance, Kruskal-Wallis, Mann Whitney U and Tukey HSD tests were performed. These analyses were conducted in order to assess the students’ attitudes towards RTRHK course and their teachers in terms of different variables. As a result, it was found that students’ attitudes towards RTRHK course was significantly differed in terms of gender, teacher’s gender, taking private lesson or going to private training center, materials used by the teacher, reading historical novels, watching historical movies, frequency of reading book, their attitudes towards their teachers, and most or least favorite course. However, it didn’t differed in terms of , parent’s educational background. Finally, when the relationship between academic achievement and these variables, a significant relationship was found between academic achievement and all of these variables except for gender.